سوشل میڈیا اور معاشرتی رویوں میں اخلاقی تربیت : سیرۃ النبی صلى الله عليه وسلم کی روشنی میں: Social Media and Moral Training in Societal Attitudes: In the Light of the Seerah (Al-Aasar, 2025)
In the contemporary era, social media has redefined communication and information dissemination; however, its misuse has led to the erosion of moral values, the spread of misinformation, and various societal challenges. This study aims to explore the potential of social media as a means to promote Islamic teachings and moral values, particularly in the light of the Prophetic Seerah ﷺ. The research employs a comparative and analytical approach using Quranic verses, Prophetic traditions, and modern sociological literature. Findings reveal that social media can be an effective platform for education, truth, social reform, and the dissemination of positive narratives. The study emphasizes the need for the state to promote responsible use of social media through training programs, legislation, and ethical regulations. Furthermore, by integrating social media ethics into the educational curriculum, the moral development of the younger generation can be enhanced. Thus, guided by the teachings of the Prophet Muhammad ﷺ, social media can be transformed from a source of harm into a powerful tool for societal reform.